The Efficacy and Adverse Effects of SORAFENIB in patiants of Hepatocellular Carcinoma in AL-Beiruny University Hospital - ديوب آصف (Latakia University Journal -Medical Sciences Series, 2021)
Background: Hepatocellular carcinoma is one of the most common types of cancer and its treatment depends on the clinical stage, tumor extension, hepatic function, and associated pathologies. Treatments vary by surgery, liver transplantation, or local treatments such as cryotherapy, intra-arterial injection or radiotherapy, and systemic therapy can be used. Sorafenib is the only treatment given as a first line in advanced or metastatic HCC. Studies have shown that administration of sorafenib has given benefit in terms of response, disease control and overall survival, especially when it is Child-Pugh A. The aim of this study: The research aims to study the efficacy and adverse effects of SORAFENIB in patients with HCC Methods: An interventional study of a clinical trial model was conducted i at Al-Biruni University Hospital in 2010 on 32 patients. Results: 32 patients with hepatocellular carcinoma participated in the study, 85% male and 15% female, who were followed up in two phases after application at 3 months and 6 months. Within 3 months (37.5%) partial response, (28.12%) remission, and disease progression (21.87%) After 6 months (15%) complete response, (25%) partial response (28.12%) stable disease and (12.5%) disease progression. Hand and foot skin reactions (37.5%) and diarrhea (31.25%) were the most common adverse effects. Conclusion: Sorafenib is a valid treatment option for advanced liver cancer. Dose reduction is still a better solution to side effects than stopping or replacing the drug, and deserves further extensive studies